Problem-Based Learning Approach with Supported Interactive Multimedia in Physics Learning: Its Effects on Critical Thinking Abilty - Yeni Rima Liana; Puji Iman Nursuhud (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
In this research, interactive multimedia on dynamic electricity concepts was developed and tested. The purpose of this research was to analyze the feasibility and the effectiveness of interactive multimedia through a problem-based learning approach to students’ critical thinking ability. The research and development (R & D) had three stages: preliminary study, development, and field testing. The field testing was a quasi-experiment with a pretest and posttest control group design. The research subjects consisted of four lecturers as expert validators, two teachers and two groups of 72 students in a senior high school in Batang Regency, Central Java. Data were gathered by using questionnaires, observation, interviews, and written test. The results of the Normalized-gain test were 61.79 for the experiment group and 49.91 for the control group. This shows that there were differences in the increase of students' critical thinking ability between the control group and the experiment group.Therefore, it can be concluded that the application of interactive multimedia could improve students' critical thinking ability.